Synthesis and Characterization of Novel Bis-Schiff Bases Based O-Tolidine - Mustafa A-Jabbar Al-Jumaili (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Three novel Schiff base (A-C) was reported in this study by reaction of o-tolidine with three different aldehydes 2-bromobenzaldehyde, 3-hydroxybenzaldehyde, and 2,4-dihydroxybenzaldehyde to attain three novel Bis-Schiff Bases ligands in high yield (86-97%). Thin-layer chromatography (TLC) technique is used to monitor the reaction. These agents were characterized by 13C, 1H NMR, HRMS, FTIR, and melting point. The synthesized tcompounds (A-C) are expected to have considerable biological activity owing to their molecular structure, which incorporates essential imine functional groups.